Evolution and predictive factors of quality of life in patients undergoing oncologic surgery for head and neck cancer: A prospective multicentric study. (March 2019) - Bozec, Alexandre; Schultz, Philippe; Gal, Jocelyn; Chamorey, Emmanuel; Chateau, Yann; Dassonville, Olivier; Poissonnet, Gilles; Demard, François; Peyrade, Frédéric; Saada, Esma; Benezery, Karen; Leysalle, Axel; et al.
Abstract: Objectives: The purposes of this study were to assess the evolution of quality of life (QoL) in patients with head and neck squamous cell carcinoma (HNSCC) undergoing oncologic surgery and to determine the predictive factors of post-therapeutic QoL. Methods: All HNSCC patients who underwent primary surgery, between 2012 and 2014, were enrolled in this prospective multicentric study. Patients completed the EORTC QLQ-C30 and QLQ-H&N35 questionnaires before surgery and at 6 months after treatment. Predictive factors of post-therapeutic QoL scores were determined. Results: A total of 200 patients were included in this study. There was no significant deterioration of global QoL and no significant increase in general symptoms between the pre- and post-therapeutic periods, but a significant deterioration in role and social functioning, and an increase of most head and neck symptoms. Tumor stage, tumor site and treatment modalities (type of surgery, adjuvant therapy) were the main predictors of QoL scores. We found a negative correlation between satisfaction with the information received and global QoL score or several functioning scales. Conclusion: HNSCC surgical treatment affects patients QoL mainly by increasing head and neck symptoms, which results in social and role functioning deterioration. These results are of great interest to improve multidisciplinary care of HNSCC patients. Highlights: Global QoL score remained stable in HNSCC patients undergoing primary oncologic surgery. A post-treatment deterioration of role and social functioning was observed. Financial problems and most head and neck symptoms increased after treatment. Tumor stage/site and treatment modalities were the main predictors of post-treatment QoL scores. We found a negative correlation between satisfaction with the information received and global QoL.